Implementation of Therapeutic and/or Abuse Drug Analysis in Blood Samples via Chemiluminescent Immunoassay Technique using the Randox Evidence Investigator™ Equipment (London Journal of Research In Science: Natural and Formal, 2024)
The Toxicology Laboratory of the Instituto Nacional de Ciencias Forenses de Guatemala -INACIF- is responsible for analysing the biological signs in the search for chemical substances, among which drugs are found. Because Laboratories constantly need to update their technology, it was necessary to implement a new chemiluminescence immunoassay technique using the Randox Evidence Investigator TM kit. This technique is useful as it provides accurate and reproducible results. To implement this technique, 10 blood samples with a positive result for drugs habitually detected in the Toxicology Laboratory and 10 blood samples with a negative result for drugs were analysed, said analysis gave as a result the fulfilment of what was expected for positive and negative drugs. The time invested in analysis was also evaluated, which was approximately 4 to 4.5 hours.
Keywords: Drug; Blood; Immunoassay; chemiluminescence; biochip